The experiential learning toolkit blending practice with concepts - Beard, Colin (Colin M.) (IG library, 2010)
Presents a range of practical exercises, which are based on the theory of experiential learning. This title features an activity that includes a description of the underlying principles, practical information on delivering the exercise as well as tips and further reading